Management of Periprosthetic Osteolysis after Total Ankle Arthroplasty - Yoo Jung Park MD (Foot & Ankle Orthopaedics, 2020)
Category: Ankle Arthritis; Ankle Introduction/Purpose: Periprosthetic osteolysis in total ankle arthroplasty (TAA) is a substantial problem. It may cause implant failure and has potential to affect long-term implant survival. To prevent major revisional arthroplasty, it is important to make an early diagnosis of osteolysis and decide an appropriate timing of surgical intervention such as bone graft. We report our updated result of bone graft for osteolysis after TAA associated with clinical and radiologic outcome. Methods: We retrospectively evaluated our consecutive series of 440 primary TAAs performed between May 2004 and August 2018 and identified those who had a subsequent bone graft procedure. A total of 38 bone graft procedures for periprosthetic osteolysis after TAA were performed. Mean time-interval between primary TAA and bone graft was 5.09 years (range 17.0 to 127.0 months). Location of osteolysis, bone grafting method and clinical outcome parameters using visual analog scale (VAS), American Orthopaedic Foot & Ankle Society (AOFAS) score were recorded. Results: Radiographs revealed periprosthetic osteolysis in 51.8% (58/112) of distal tibial lesions and 41.1% (46/112) of talar lesions. Autogenous iliac bone graft was used in most of procedures. Both mean VAS and AOFAS scores improved significantly at the last follow-up (p<0.05) One patient needed a repeat bone graft procedure with additional bone cementation after the primary bone grafting due to large cyst on distal tibia. There was no implant failure or major revisions after the bone graft. Conclusion: Bone graft for periprosthetic osteolysis may improve patient’s clinical outcome and give support to the structures surrounding the implant. Bone grafting in optimal timing may also improve implant survivorship. However, further study is needed for the etiology of newly developed painless osteolysis even after the bone graft.